In-Plane Thermal Diffusivity Measurements of Polyethersulfone Woven Textiles by Infrared Thermography - Mariacristina Larciprete; Noemi Orazi; Yves-Simon Gloy; Stefano Paoloni; Concita Sibilia; Roberto Li Voti (Sensors, 2022)
Lock-in thermography was applied to the measurement of the in-plane thermal diffusivity of three polyethersulfone (PES) textiles characterized by different weaving pattern as well as different mass density of interlacing fibers. The experimental results showed that the in-plane thermal diffusivity in each direction decreased with the increase of the fibers’ linear mass density, thus leading to an anisotropic behavior of the thermal diffusivity in the specimen where PES fibers with different density were interlaced. A new theoretical model for the study of the heat diffusion in textiles was specifically developed and, thereafter, employed for the analysis of the experimental results. As such, our textile model approach, shedding light on the role of different textile and fibers parameters on the resulting thermal diffusivity, paves the way for the development and design of textiles with tailored thermal behavior.